Fear in business-to-business relationships - Bignoux, Stephane; Golgeci, Ismail; Capar, Nejat (Elsevier, 2026)
Research on the dark side of business-to-business (B2B) relationships has largely focused on problematic relationships and coordination dynamics, such as opportunism, dependence, and power asymmetries, while the role of negative emotions, like fear, remains underexplored. This paper addresses this gap by theorizing fear as a distinct dark side emotion in B2B relationships. We conceptualize fear as a cognitively grounded emotional response arising from boundary spanners' threat perceptions, shaped by individual-level mechanisms such as threat detection, memory, and mental models. Drawing on psychology, neuroscience, and marketing literature, we develop a multilevel framework that explains how fear emerges at the individual level, propagates across B2B relationships, and is amplified by relationship salience. We further theorize that fear triggers dyadic responses primarily manifested as distancing behaviors or coordination strategies, thereby constraining collaboration and innovation. We position fear as a dark-side emotion with distinct antecedents, manifestations, and outcomes, advance the microfoundations of B2B relationships, and extend the dark-side literature beyond structural and behavioral dysfunctions. The framework also provides a foundation for future empirical research on how negative emotions destabilize B2B relationships in volatile and uncertain business environments.
Keywords: Fear; B2B relationships; Emotion contagion; Boundary spanners; fi=Kansainvälinen liiketoiminta|en=International Business|